HadGEM2-CC model output prepared for CMIP5 RCP4.5, served by ESGF - Osprey, S; Hardiman, S (WDCC at DKRZ, 2014)
rcp45 is an experiment of the CMIP5 - Coupled Model Intercomparison Project Phase 5 (http://cmip-pcmdi.llnl.gov/cmip5/). CMIP5 is meant to provide a framework for coordinated climate change experiments for the next five years and thus includes simulations for assessment in the AR5 as well as others that extend beyond the AR5.